Assessment of microplastic content in Diadema africanum sea urchin from Tenerife (Canary Islands, Spain). (February 2022) - Sevillano-González, Marta; González-Sálamo, Javier; Díaz-Peña, Francisco J.; Hernández-Sánchez, Cintia; Catalán Torralbo, Sergio; Ródenas Seguí, Airán; Hernández-Borges, Javier
Abstract: Sea urchins are highly abundant in the marine ecosystem where they graze limiting algal biomass and also serving as food for other predators. In this work, the presence of microplastics in the digestive tracts and gonads of 33 Diadema africanum sea urchins collected at two sampling points in Tenerife (Canary Islands, Spain) was studied. After separation and digestion of the digestive tracts and the gonads, the visualization of the filtrates under the stereomicroscope revealed the presence of 320 items which were microfibers (97.5%), fragments (1.9%) and films (0.6%), mainly blue (43.3 and 47.0% in the two sampling points, Tajao and El Porís, respectively) and translucent white (32.5 and 39.5%, respectively). Statistical analysis revealed that there were no significative differences in the contents of gonads and digestive tracts between both sampling locations. Regarding microfibers lengths, significative differences were only observed between the two sampling points, not between tissues. μRaman analysis showed that they were mainly cellulosic (46.0%), polypropylene (24.3%) and polyethylene terephthalate (24.3%). This study confirms for the first time the presence of microplastics in sea urchins from the Macaronesian region and also from Spain. Graphical abstract: Unlabelled Image Highlights: First evidence of microfibers presence in sea urchins of the Canary Islands (Spain). 9.2 ± 3.0 items/individual and 10.0 ± 4.5 items/individual were found in the two sampling points. Microfibers were the most abundant (97.5%) which were mainly blue and translucent white. μRaman analysis showed that most of the fibers were cellulosics, PP and PET.